2013
DOI: 10.1007/s10856-013-4915-4
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorods mediated controlled release of doxorubicin: nano-needles for efficient drug delivery

Abstract: Use of cysteamine hydrochloride (Cys-HCl) protected gold nanorods (GNRs) as efficient carrier of widely used anti-cancer drug doxorubicin using folic acid as navigational molecule is presented in this work. GNRs were found to have excellent drug loading capacity of >97 %. A detailed comprehension of in vitro drug release profile under ideal physiological condition was found to obey 1st order kinetics at pH 6.8, 5.3 and 7.2, an ideal milieu for drug delivery to solid tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Therefore, folate is widely used as a targeting ligand which specifically binds to folate receptors on the tumor cell surface and internalized by the cancer cells. Gold nanoparticles loaded by different cytotoxic agents or photosensitizer conjugated with folate have been developed by many researchers, enhancing cancer cell accumulation of drug, improving the cytotoxicity of the anticancer agents overcoming anticancer drug resistance [182][183][184]. The glucocorticoid responsive genes, a specific category of "endogenous" genes, upregulate in only cancer cells [185].…”
Section: Targeted Delivery Systems Based On Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, folate is widely used as a targeting ligand which specifically binds to folate receptors on the tumor cell surface and internalized by the cancer cells. Gold nanoparticles loaded by different cytotoxic agents or photosensitizer conjugated with folate have been developed by many researchers, enhancing cancer cell accumulation of drug, improving the cytotoxicity of the anticancer agents overcoming anticancer drug resistance [182][183][184]. The glucocorticoid responsive genes, a specific category of "endogenous" genes, upregulate in only cancer cells [185].…”
Section: Targeted Delivery Systems Based On Gold Nanoparticlesmentioning
confidence: 99%
“…Targeted drug delivery in vitro and in vivo [186] Large surface [182,184,186,195] Journal of Nanomaterials…”
Section: Specific Functionalized Gnpsmentioning
confidence: 99%
“…120 It was reported that spherical AuNPs increased the cellular uptake when compared to rod-shaped Table 4 The current applications of gold nanoparticle-loaded anticancer drugs in drug delivery systems AuNPs 106,115 probably due to the elongated particles requiring longer time for membrane wrapping. 121 Despite the fact there were some previous studies reported that rod-shaped AuNPs enhanced the therapeutic outcomes in cancer drug delivery, including prolonged circulation times 122 and enhanced drug loading, 123 it is also important to note that the synthesis of gold nanorods requires the use of a growth-directing surfactant (cetyltrimethylammonium bromide, CTAB). Free CTAB without nanorods was shown to induce cytotoxicity in the human colon cancer HT-29 cell line.…”
Section: Design Of Gold Nanoparticles For Cellular Uptakementioning
confidence: 99%
“…Similarly drug release studies were also carried out at pH 6.8 and 7.4. The experiments were performed in triplicate for each of the samples and drug release kinetics was studies using Zero order, First order, Higuchi and Hixson-Crowell pharmacokinetics model according to our previous studies [18,19].…”
Section: In-vitro Drug Release Studiesmentioning
confidence: 99%